Understanding The Meaning Of Water Zam-Zam In Hadits (With A Scientific Approach) - Sintia, Dita (UNIVERSITAS PAKUAN, 2025)
Zam-Zam water has a special position in Islamic teachings and is mentioned in various hadiths of the Prophet as water that is full of blessings, a cure for diseases, and in accordance with the intentions of the drinker. This article aims to explore the meaning of Zam-Zam water in the hadith through a multidisciplinary approach, especially a scientific approach. Using a qualitative method based on literature studies, the author analyzes a number of authentic hadiths and scientific studies on the composition and characteristics of Zam-Zam water. The findings show that spiritually, this water has strong symbolism in the theological construction of Islam, while from a scientific perspective, the mineral content, pH balance, and hygienic properties of Zam-Zam water show relevance to its claimed health benefits. This study concludes that an integrative approach between revelation and science not only strengthens understanding of religious texts, but also opens up space for constructive dialogue between Islam and modern science.